Implementing Islamic Financial Literacy to Foster Saving Habits in Early Childhood - Patimah; Uswah Hasanah (Al-Qalam Institue, 2026)
Sharia financial literacy plays a strategic role in shaping responsible financial behavior aligned with Islamic values from an early age. The habit of saving is a relevant form of implementing Sharia financial literacy to instill a sense of trustworthiness, self-control, and awareness of wise wealth management. In the context of early childhood education, the application of Sharia financial literacy needs to be contextualized and sustainable so that the introduced values can be internalized in children's daily behavior. This study used a qualitative descriptive method with a case study approach conducted at Tadika Didik Bistari Gemilang Malaysia. Data were obtained through observation of learning activities, in-depth interviews with the headmaster, class teachers, parents, and children aged 5–6, and supported by documentation of activities. The study results indicate that Sharia financial literacy is implemented through the habit of saving integrated into children's learning activities, such as direct practice of saving and the use of simple media appropriate to the child's developmental stage. This hands-on, experience-based approach increases children's engagement and helps them understand the concrete meaning of saving. Consistently practicing these habits has a positive impact on children's behavior, as reflected in increased savings habits, greater caution in using pocket money, and the ability to delay desires. These findings confirm that Islamic financial literacy, implemented from an early age, plays a crucial role in developing potentially responsible and sustainable financial behavior when supported by synergy between the school and family environments.